2013
DOI: 10.1186/1471-2407-13-144
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of Cancer/Testis Antigens in cancer is associated with distinct patterns of DNA Hypomethylation

Abstract: BackgroundThe Cancer/Testis Antigens (CTAs) are a heterogeneous group of proteins whose expression is typically restricted to the testis. However, they are aberrantly expressed in most cancers that have been examined to date. Broadly speaking, the CTAs can be divided into two groups: the CTX antigens that are encoded by the X-linked genes and the non-X CT antigens that are encoded by the autosomes. Unlike the non-X CTAs, the CTX antigens form clusters of closely related gene families and their expression is fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 47 publications
4
34
0
Order By: Relevance
“…Indeed, hypomethylation-associated CTA expression was observed for established X chromosomal CTAs and novel non-X chromosomal CTAs in around one-third of our NSCLC CTA list. This is in line with previous studies suggesting that epigenetic regulation is one major regulatory mechanism of CTA activation (35,42,43).…”
Section: Figure 9 Network Analysis Of Cancer Testis Antigens (Ctas) supporting
confidence: 81%
“…Indeed, hypomethylation-associated CTA expression was observed for established X chromosomal CTAs and novel non-X chromosomal CTAs in around one-third of our NSCLC CTA list. This is in line with previous studies suggesting that epigenetic regulation is one major regulatory mechanism of CTA activation (35,42,43).…”
Section: Figure 9 Network Analysis Of Cancer Testis Antigens (Ctas) supporting
confidence: 81%
“…We found that the human MAEL gene is only expressed in germ cells of the testis among normal tissues, but is expressed in various human cancer cell lines such as breast cancer MDA-MB-231 cells and colorectal cancer SW480 cells. Like most of the CT genes (15,16), the expression of the MAEL gene is activated by hypomethylation in cancer (12). Kim et al (17) analyzed the methylation profile of 27,578 CpG sites spanning >14,000 genes in colorectal cancer and adjacent normal mucosa, and found that among the genes tested, MAEL and SFT2D3…”
Section: Introductionmentioning
confidence: 98%
“…PASD1 is not expressed in cells of somatic origin unless it has been de-repressed due to malignant transformation (Kim et al, 2013). The circadian clock is frequently disrupted in cancer, allowing cells to escape its daily temporal control of regulated processes and facilitate tumor growth (Filipski and LĂ©vi, 2009; Sahar and Sassone-Corsi, 2009; Takahashi et al, 2008).…”
Section: Resultsmentioning
confidence: 99%